Motivational tips for at-risk students - Renetzky, Alvin; Arsenault, Richard (Santa Monica, CA : Educator's Choice, 1993)
Motivation is often the key to turning at-risk students into successful students. This program shows at-risk teens the steps necessary to become self-motivated
Title from title screen
Executive producer, Alvin Renetzky, Cheryl Renetzky
Keywords: Motivation in education; Underachievers; Slow learning children; Remedial teaching